Purification and Characterization of a Cellular Protein That Binds to the Downstream Activation Sequence of the Strict Late U(L)38 Promoter of Herpes Simplex Virus Type 1 - Petroski, Matthew D. (American Society for Microbiology, 1998)
Previous work on the strict late (γ) U(L)38 promoter of herpes simplex virus type 1 identified three cis-acting elements required for wild-type levels of transcription: a TATA box at −31, a consensus mammalian initiator element at the transcription start site, and a downstream activation sequence (DAS) at +20 to +33. DAS is found in similar locations on several other late promoters, suggesting an important regulatory role in late gene expression. In this communication, we further characterize the interaction between DAS and a cellular protein which is found in both uninfected and infected nuclear extracts. This protein was purified from HeLa nuclear extracts and identified as the DNA binding component (Ku heterodimer) of DNA-dependent protein kinase (DNA-PK) by peptide mapping. Highly purified DNA-PK was able to stimulate U(L)38 transcription in vitro approximately 10-fold. DAS is similar in sequence to another element, nuclear regulatory element 1 (NRE1) of the glucocorticoid-responsive mouse mammary tumor virus long terminal repeat. NRE1 is known to specifically bind Ku in the absence of DNA ends. We demonstrated that NRE1 is able to substitute for DAS in the U(L)38 promoter to activate transcription as measured by in vitro transcription and in vivo during infection of tissue culture cells with recombinant virus. Also, we found that the binding of DNA-PK to DAS involves the bases demonstrated to be important in U(L)38 transcription and that the 70-kDa subunit of Ku binds to DAS.